Cuprous Ion Mass Transport Limitations During Copper Electrodeposition. Issue 8 (1st June 2017) - Schmidt, Ralf; Gaida, Josef
Abstract: Polarization experiments in sulfuric acid based copper plating electrolytes disclosed unique mass‐transport limitations at very small cathodic overpotentials. Determination of the bulk concentration of the species, which is correlated to the observed limiting current plateaus, by means of Levich plots indicated that these plateaus may be related to mass‐transport‐limited copper deposition from cuprous ions. This hypothesis was further supported by comparison of the equilibrium constant of the comproportionation of cupric ions and metallic copper to cuprous ions obtained from experiments with literature values. The results provide a simple technique to detect cuprous ions and support the view that cuprous ions are deposited at a diffusion‐limited rate, whereas cupric ions deposition is controlled by electrochemical kinetics. The method may be of relevance for superfilling, since the action of additives in industrial plating electrolytes involves interaction with cuprous ions. Abstract : Experimental detection of cuprous ions during electrodeposition of copper from cupric ions is of relevance for industrial plating electrolytes but usually requires elaborate techniques. The method described herein provides a simple manner to measure the cuprous ion bulk concentration employing a standard rotating disc electrode.